2016
DOI: 10.1158/1557-3125.cellcycle16-b14
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B14: Feedback regulation between atypical E2Fs and APC/CCdh1 coordinates cell cycle progression.

Abstract: E2F transcription factors control the oscillating expression pattern of multiple target genes during the cell cycle. Activator E2Fs, E2F1-3, induce an upswing of E2F targets, which is essential for the G1-to-S phase transition, whereas atypical E2Fs, E2F7 and E2F8, mediate a downswing of the same targets during late S, G2, and M phase. Expression of atypical E2Fs is induced by E2F1-3, but it is unknown how atypical E2Fs are inactivated in a timely manner. Using molecular assays, time lapse microscopy, and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Here, we show a novel mechanism for how the repressor activity of atypical E2Fs can be inhibited through direct phosphorylation by Chk1 which provides a docking station for 14‐3‐3 proteins to interact with E2F7 and E2F8 (Fig D). Previous studies have demonstrated that increased repressor activity of atypical E2Fs downregulates the expression of a large number of cell cycle genes resulting in a severe cell cycle arrest accompanied by increased DNA damage and apoptotic events (de Bruin et al , ; Maiti et al , ; Westendorp et al , ; Boekhout et al , ). Our findings provide strong evidence for a regulatory mechanism that suppresses the atypical E2F activity in order to avoid detrimental effects on cell cycle progression and cell survival under DNA‐damaging conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we show a novel mechanism for how the repressor activity of atypical E2Fs can be inhibited through direct phosphorylation by Chk1 which provides a docking station for 14‐3‐3 proteins to interact with E2F7 and E2F8 (Fig D). Previous studies have demonstrated that increased repressor activity of atypical E2Fs downregulates the expression of a large number of cell cycle genes resulting in a severe cell cycle arrest accompanied by increased DNA damage and apoptotic events (de Bruin et al , ; Maiti et al , ; Westendorp et al , ; Boekhout et al , ). Our findings provide strong evidence for a regulatory mechanism that suppresses the atypical E2F activity in order to avoid detrimental effects on cell cycle progression and cell survival under DNA‐damaging conditions.…”
Section: Discussionmentioning
confidence: 99%
“…E2F7 and E2F8 levels peak during S phase, to mediate the downswing of many oscillating target genes involved in DNA replication, metabolism, and DNA repair. We previously found that E2F7 and E2F8 are subjected to degradation via APC/C Cdh1 during G1 phase, to allow a time window for upregulation of E2F target genes by activator E2Fs, and subsequent S‐phase entry (Boekhout et al , ). Meanwhile, ectopic expression of E2F7 and E2F8 is sufficient to stall S‐phase progression, indicating that their activity must be carefully regulated to ensure unperturbed proliferation (Westendorp et al , ; Boekhout et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic expression of atypical E2Fs leads to downregulation of these target genes accompanied by a permanent Sphase arrest and severe DNA damage (Westendorp et al, 2012;Yuan et al, 2018). Recently, we have shown that APC/C Cdh1 targets E2F7 and E2F8 for degradation during the G1 phase of the cell cycle and that inhibition of the APC/C Cdh1 -mediated degradation of E2F7 and E2F8 impairs S-phase entry, eventually resulting in cell death (Boekhout et al, 2016). As such, activity of E2F7 and E2F8 must be tightly regulated during the cell cycle and in response to DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, the regulatory mechanism behind the downregulation in G2 is unknown (Boekhout et al, 2016). However, the regulatory mechanism behind the downregulation in G2 is unknown (Boekhout et al, 2016).…”
Section: Introductionmentioning
confidence: 99%